A ‘slow pace of life’ in Australian old-endemic passerine birds is not accompanied by low basal metabolic rates (2016)
Life history theory suggests that species experiencing high extrinsic mortality rates allocate more resources toward reproduction relative to self-maintenance and reach maturity earlier (‘fast pace of life’) than those having greater life expectancy and reproducing at a lower rate (‘slow pace of life’). Among birds, many studies have shown that tropical species have a slower pace of life than temperate-breeding species. The pace of life has been hypothesized to affect metabolism and, as predicted, tropical birds have lower basal metabolic rates (BMR) than temperate-breeding birds. However, many temperate-breeding Australian passerines belong to lineages that evolved in Australia and share ‘slow’ life-history traits that are typical of tropical birds. We obtained BMR from 30 of these ‘old-endemics’ and ten sympatric species of more recently arrived passerine lineages (derived from Afro-Asian origins or introduced by Europeans) with ‘faster’ life histories. The BMR of ‘slow’ temperate-breeding old-endemics was indistinguishable from that of new-arrivals and was not lower than the BMR of ‘fast’ temperate-breeding non-Australian passerines. Old-endemics had substantially smaller clutches and longer maximal life spans in the wild than new arrivals, but neither clutch size nor maximum life span was correlated with BMR. Our results suggest that low BMR in tropical birds is not functionally linked to their ‘slow pace of life’ and instead may be a consequence of differences in annual thermal conditions experienced by tropical versus temperate species. © 2016, Springer-Verlag Berlin Heidelberg.